2003
DOI: 10.1530/eje.0.1480559
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of activin and follistatin are elevated and run in parallel in patients with septicemia

Abstract: Objective: Activin is a growth and differentiation factor of many cell types, and has recently been implicated in inflammatory processes. Clinical data linking activin and its binding protein, follistatin (FS), are lacking. We measured serum levels of activin and FS in patients diagnosed with septicemia. Patients and measurements: Eight male and seven female patients of different ages, various forms of septicemia and different clinical outcome were investigated and compared with age-and sex-matched healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 51 publications
6
55
0
1
Order By: Relevance
“…A similar pattern of expression during infections has been observed for other immunomodulatory cytokines, such as IL-10 and transforming growth factor-β 1 (27). In agreement with our findings, other studies have demonstrated that activin-A is elevated in the circulation during septicemia in adults and associated with the severity of inflammation (28). Moreover, activin-A is increased in the cerebrospinal fluid during meningitis in animal models and adults (22,23).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A similar pattern of expression during infections has been observed for other immunomodulatory cytokines, such as IL-10 and transforming growth factor-β 1 (27). In agreement with our findings, other studies have demonstrated that activin-A is elevated in the circulation during septicemia in adults and associated with the severity of inflammation (28). Moreover, activin-A is increased in the cerebrospinal fluid during meningitis in animal models and adults (22,23).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, activin-A is increased in the cerebrospinal fluid during meningitis in animal models and adults (22,23). Serum levels of activin-A vary with certain studies reporting high levels (11,29) and other studies reporting similar levels, or even, reporting lower levels to our study (9,28,30,31). This discordance could be due to the differences in the experimental set up, including the age of the neonates studied, the disease context, the methodology employed, the time point of analysis, etc.…”
Section: Discussionmentioning
confidence: 54%
“…[35][36][37][38][39] Accordingly, elevated activin A levels have been observed in a mouse model of endotoxemia and in patients with clinical sepsis condition. 22,40 Furthermore, treatment with FS increased the survival of mice that were lethally challenged with LPS, 22 supporting the role of activin A as an early proinflammatory mediator in these models.…”
Section: Monocytesmentioning
confidence: 87%
“…In animals, ActA increases quickly in circulation in response to acute inflammatory stimulus, such as an lipopolysaccharide (LPS) injection 34. In humans, elevated ActA levels have been observed in several inflammatory diseases, such as septicemia35 or acute distress syndrome,36 and are associated with the severity of the disease and poor prognosis. Neoplastic process is associated with systemic inflammation, mediated by several cytokines such as IL‐1β, IL‐6, TNFα, and ActA 37, 38.…”
Section: Discussionmentioning
confidence: 99%